Pencegahan Infeksi Nosokomial Berhubungan Dengan Teori Nightingale - Cesaltina Bui Pereira; Priyanto Priyanto (Pusat riset dan Inovasi Nasional, 2026)
Nosocomial infections, also known as Healthcare-Associated Infections (HAIs), are infections acquired by patients during their stay in healthcare facilities. These infections remain a serious problem because they can increase morbidity and mortality rates, prolong the length of hospital stay, and raise healthcare costs. One classical yet highly relevant approach to preventing nosocomial infections is Florence Nightingale’s Environmental Theory. This theory emphasizes the importance of maintaining a clean environment, adequate ventilation, proper lighting, effective sanitation, and good personal hygiene to support patient recovery and reduce infection risks. Nightingale believed that environmental factors play a crucial role in improving patient health outcomes and preventing disease transmission. In modern nursing practice, the principles of Nightingale’s theory are still widely applied through infection prevention and control programs, environmental cleanliness standards, and patient-centered care. Therefore, understanding and implementing environmental management in healthcare settings remain essential strategies to reduce nosocomial infection rates and improve the overall quality of healthcare services.